ANALISA PERANCANGAN PEMBANGKIT LISTRIK TENAGA SURYA PADA RUMAH TINGGAL DI PONDOK 6 - Pohan, M Yasir; Pinayungan, Doni; Zambak, M.Fitra; Hardi, Surya; Suwarno, Suwarno; Rohana, Rohana; Warman, Eddy (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
n the development of Indonesia, both the past mass and the energy front mass will continue to make changes and developments. This is due to developments and innovations in the use of renewable energy. Likewise with PLTS, which has developed quite a message and also continues to experience fairly rapid development, not only industry but also PLTS can be developed for home-scale or small-scale energy users. This is because the use of PLTS is quite efficient, both in terms of construction costs and maintenance costs.